Concepts “War” and “Peace” In English Linguo-Culture and Units Denoting Them (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article deals with one of the most popular concepts in modern English linguo-culture; that is a concept “war and peace”. As we know a concept is a linguo-philosophical unit that was introduced thanks to an anthropocentric approach in linguistics. Lexical units that denote concepts “war and peace” in linguo-culture in the English language are analyzed in this article. Specific theoretical and practical characteristic features of these terms are thoroughly discussed in the article.